Molecular characterization of embryonic stem cell-derived cardiac neural crest-like cells revealed a spatiotemporal expression of an Mlc-3 isoform - Mellein, Stefanie; Rappold, Gudrun; Niesler, Beate (International Journal of Stem Cells, 2020)
Stefanie Schmitteckert, Cornelia Ziegler, Gudrun A. Rappold, Beate Niesler, Alexandra Rolletschek. IJSC 2020;13:65-79. https://doi.org/10.15283/ijsc19069